Multimodal Construction of Social Values in Zootopia 2: A Semiotic Analysis of the Official Poster and Soundtrack Lyrics - Rangga Permana; Dery Purnama Saefudin; Siti Nurani; Elisabeth Vita Mutiarawati; Adah Puadah (Universitas Muria Kudus, 2026)
This study examines how verbal and visual semiotic resources interact in the promotional materials of Zootopia 2 to construct social meanings and ideological messages. Drawing on Barthes’ concepts of denotation, connotation, and myth and Kress and van Leeuwen’s multimodal framework, the study employs a qualitative multimodal semiotic approach to analyze the official movie poster and soundtrack lyrics. Data were analyzed through iterative coding focusing on representational, interactive, and compositional meanings across verbal and visual modes. The findings reveal three interconnected themes: diversity and inclusivity, collective resilience and cooperation, and optimism and self-actualization. The lyrics promote social inclusion, collaboration, and personal empowerment through explicit linguistic expressions, while the poster reinforces these meanings through character positioning, visual composition, color, and symbolic representation. The interaction between verbal and visual signs constructs a broader cultural narrative that presents diversity as a social asset, resilience as a collective process, and optimism as a pathway to personal growth. The study contributes to multimodal semiotic scholarship by demonstrating how promotional media function not only as marketing tools but also as cultural texts that communicate social values and ideological meanings through the integration of multiple semiotic resources.